Hubungan pola asuh dengan kejadian stunting balita dari keluarga miskin di Kota Palembang - Bella, Febriani Dwi; Fajar, Nur Alam; Misnaniarti, Misnaniarti (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2019)
Background: Nutritional problems do not always occur in poor families, in fact many of under five years in poor families in good nutritional status which have normal height (not stunting) based on the parenting in the family. The positive parenting in poor families are feeding habit, parenting habit, hygiene habit and health services habit. Objectives: This research aim to observe the parenting of feeding habits, parenting habits, hygiene habits and health services habits on the incidence of toddler’s stunting on poor families in the city of Palembang.Methods: This research was an observational study which using a quantitative approach with a Cross Sectional Study design. It took 100 mothers who have children aged 24-59 months from poor families in the city of Palembang were chosen by proportional random sampling.Data taken regarding feeding habits, parenting habits, hygiene habits, and health services habits obtained through questionnaires, and the incidence of child stunting obtained from measurements of children's height using a toddler's height measurement tool. Data analysis to observe the relationship between variables using the Chi-Square test.Results: The results showed the proportion of toddler stunting in poor families in the city of Palembang was 29%. There was a significant correlation between feeding habits (p-value = 0.000); parenting habits (p-value = 0.001; hygiene habits (p-value = 0.021) and health services habits (p-value = 0.000) on the incidence of toddler’s stunting.Conclusion: Normal height (not stunting) toddlers have positive deviance of feeding habits, parenting habits, hygiene habits and health services habits better than stunting under five years with same economic backgrounds family